Constitutional Complaint in Ukraine: The Interrelation Between the Protection of Subjective Civil Rights and Constitutional Control - Krupchan, Oleksandr D.; Kochyn, Volodymyr V.; Zaporozhets, Vitalii I.; Bernatskyi, Mykyta V. (International Journal of Criminology and Sociology, 2021)
The real possibility of judicial protection of individual rights and freedoms is a key element of effective legal regulation, as well as the manifestation of the rule of law. The new institution of the constitutional complaint lies in a rather specific plane, being both a part of the national system of protection of individual rights and freedoms and an element of constitutional control that ensures the supremacy of the Constitution of Ukraine. The relevance of this study is conditioned by the right of a citizen to complain about the mechanism of legal regulation, taking the provisions of the Constitution as an example. The purpose of the study is to consider the specific features of the interrelation between the protection of subjective civil rights and constitutional control. This study analyses the theoretical aspects, legislative regulation, and practice of the Constitutional Court of Ukraine. It was concluded that subjective rights and interests established by law might be violated, unrecognised or challenged only at the stages of legal implementation or enforcement.